Grief among healthcare workers: A comparative study - Lerea, L Eliezer; Limauro, Barbara F (The Journals of Gerontology, 1982)
This investigation examined the prevalence and nature of grief in response to patient suffering, loss, or death among healthcare workers employed at a general hospital and a skilled nursing facility. A questionnaire was constructed for this purpose. Approximately two-thirds of the skilled nursing facility personnel remembered experiencing bereavement as a reaction to the crises of their geriatric patients. Mourning occurred among virtually all of the general hospital personnel who usually serve younger patients. Healthcare personnel mourned most often for those persons who suffered or died of cancer. A selected sample of respondents recalled that psychological symptoms of grief were more evident than physical. Both symptom types often persisted for more than 1 month. Since grief is common among nurses and aides employed at the two medical settings, bereavement counseling is suggested for those healthcare personnel who require this service.
Keywords: United States; classification; dept.csp; geriatrics; grief; health care personnel; hospital; normal human; nursing home; psychological aspect; questionnaire; therapy